Prostate cancer metastasis to the testis: an unexpected presentation of a solitary recurrence. Issue 3 (2nd March 2021) - McCann, Conor; Doherty, Anna; Flynn, Ciaran; Mulholland, Colin
Abstract : A 74-year-old man with a history of prostate cancer was referred to the urology team with a new left sided testicular lump. He had a background of prostate cancer 4 years previous which had been treated with external beam radiotherapy and androgen deprivation therapy, both of which had been completed. Concurrently, he also had evidence of biochemical recurrence of prostate cancer with a rising prostate-specific antigen (PSA). He underwent a left radical orchidectomy. Following histopathological analysis, this was found to be metastatic spread from his prostate cancer. Subsequent staging showed no evidence of metastatic spread elsewhere. The patient made a good recovery following surgery and his PSA levels returned to undetectable levels. He received no further treatment for metastatic prostate cancer.